Phylogenetic relationships and biological features reveal that male Ostrinia furnacalis (Lepidoptera: Crambidae) in Northeast China can be categorized into postmedial line-based clades - Han, Xiao; Chen, Ri-Zhao; Li, Lan-Bing; Wei, Xin; Qu, Ming-Bo; Klein, Michael G.; Wang, Ke-Qin (Zootaxa, 2020)
Ostrinia furnacalis (Guenée) (Lepidoptera: Crambidae), often called the Asian corn borer, is a complicated pest because of its complex biological features, such as its adult dynamics, host choice, and life span. This complexity has been causing difficulties in both pest forecasting and control for more than 60 years. One likely explanation for this complexity is that O. furnacalis has several varieties that vary based on some specific features. During 2015–2017, postmedial line-based varieties of male O. furnacalis were identified as distinct clades (I, II, and III), which were then compared based on COI gene sequences, male sacculus construction, life span, male dynamics, and host preference. The results showed that: (1) clades II and III were more closely related to each other than Clade I, because they both completed two generations per year, more were captured in 2016 or fewer were captured in 2015, and they were more closely related according to phylogenetic inference; (2) all three clades shared some features, such as life spans under various rearing conditions, similar dynamic trends, and three teeth on the male sacculus; and (3) all three clades were significantly different from O. nubilalis based on genetic sequences, postmedial line pattern of the forewing, and sacculus construction. Overall, if O. furnacalis is categorized into clades, the species’ features are likely to be a combination or mixture of the features of each individual clade. Our findings help explain the biological complexity of O. furnacalis. Future investigations on each individual clade are essential for improving forecasting and control of this pest.